Scanning Probe Microscopy of Topological Structure Induced Electronic States of Graphene. Issue 3 (28th January 2020) - Li, Shichao; Liu, Mengxi; Qiu, Xiaohui
Abstract: Graphene, as the first emerging 2D material, has attracted considerable attention because of its remarkable physical properties and potential applications in future electronic devices. Due to its planar structure and monoatomic thickness, graphene is susceptible to the presence of structural and topological defects in lattices, which can have a pronounced influence on the electrical, optical, thermal, and magnetic properties of this carbon allotrope. To unravel the structural disorders at the atomic scale, characterization techniques such as scanning tunneling microscopy (STM) and atomic force microscopy (AFM) have been widely employed. These techniques enable atomically resolved visualization of the lattice imperfection in graphene, as well as a simultaneous interrogation of the electronic states associated with the structural perturbations. This short review highlights the recent advances in the application of STM and AFM for investigating various defects in graphene, including vacancies, substitutional dopants, non‐hexagonal rings, 1D homo‐ and hetero‐boundaries, and stacking misorientation and faults at interlayers. The understanding of the intrinsic properties of structural and topological defects in graphene is essential for developing graphene‐based functional materials and related devices. Abstract : The properties of graphene are susceptible to structural and topological defects. Recent advances in the application of scanning tunneling microscopy and atomic force microscopy for investigating various defects in graphene are highlighted in this review, including vacancies, substitutional dopants, non‐hexagonal rings, 1D homo‐ and hetero‐ boundaries, and stacking misorientations in the interface.